Sobre la distribución de masa de la galaxia Fourcade-Figueroa - Saponara, Juliana (2021)
Here we present preliminary results on the nearby Fourcade-Figueroa galaxy (FF; D = 6.95 Mpc), located just behind the southern lobe of the radio galaxy Centaurus A (NGC 5128; D = 3.8 Mpc). By combining 21 cm observations from the Giant Metrewave Radio Telescope and the Australia Telescope Compact Array, we achieved image cubes of unprecedented quality, with a spectral resolution of 4 km s-1, an rms noise of 2 mJy beam-1 and an angular resolution of 20´´× 20´´. From the fitting of an inclined ring model to the data cubes, we obtained the FF rotation curve and its de-projected HI surface distribution. Using data from the Hubble Space Telescope we derived the corresponding surface brightness distribution of the galaxy. The rotation curve and brightness distributions were used to build the mass models for the galaxy. In this contribution we present the first results for the particular case of minimum stellar mass, and discuss what was found when considering the Navarro, Frenk and White and pseudo- isothermal dark matter halos.